Hcf and lcm, Mathematics

The HCF & LCM of two expressions are respectively (x+3) and (x cube-7x+6).

If one is x square+2x-3 , other is?

Solution)

(x+3) * (x^3-7x+6) = (x^2+2x-3) * y      () (HCF*LCM= PRODUCT OF THE TWO NUMB.)

(x+3)*(x-1)*(x^2+x-6)/(x+3)(x-1)

x^2+x-6 Ans.

Posted Date: 3/11/2013 1:27:44 AM | Location : United States







Related Discussions:- Hcf and lcm, Assignment Help, Ask Question on Hcf and lcm, Get Answer, Expert's Help, Hcf and lcm Discussions

Write discussion on Hcf and lcm
Your posts are moderated
Related Questions
How did the teacher get 30 + 12 + 1.5 for the equation of volume of rectangular prism measuring L=14.4, W= 3, and H= 5? Formula given was V= Bh. My answer was 43.5.14.5 x 3.

Illustration In a social survey whether the main reason was to establish the intelligence quotient or IQ of resident in a provided area, the given results were acquired as tab

what are reason inside a circle?

Given y = f(x) = x 2 + 2x +3 a) Use the definitional formula given below to find the derivative of the function. b) Find the value of the derivative at x = 3.

Definition of a Function Now we need to move into the second topic of this chapter.  Before we do that however we must look a quick definition taken care of.


The sum of the digit number is 7. If the digits are reversed , the number formed is less than the original number. find the number

If f(x) is an infinitely differentiable function so the Taylor Series of f(x) about x=x 0 is, Recall that, f (0) (x) = f(x) f (n) (x) = nth derivative of f(x)


product line of lg company